Emotional Reaction to Fear- and Disgust-Evoking Snakes: Sensitivity and Propensity in Snake-Fearful Respondents - Rádlová, Silvie; Polák, Jakub; Janovcová, Markéta; Sedláčková, Kristýna; Peléšková, Šárka; Landová, Eva; Frynta, Daniel (Frontiers in Psychology, 2020)
This paper continues our previous study in which we examined the respondents’ reaction to two morphologically different snake stimuli categories – one evoking exclusively fear and another evoking exclusively disgust. Here we acquired Likert-type scale scores of fear and disgust evoked by the same snake stimuli by a total of 330 respondents. Moreover, we collected data about the respondents’ age, gender, education, snake fear (Snake Questionnaire, SNAQ), and disgust propensity (Disgust Scale-Revised, DS-R), and we analyzed the effect of these variables on the emotional scores (with special focus on snake-fearful respondents). In addition to this, we collected the SNAQ and DS-R scores from the respondents tested in the previous study using the rank-ordering method to directly compare the results of these two approaches. The results showed that non-fearful respondents give high scores of fear to the fear-eliciting snakes and high scores of disgust to the disgust-eliciting snakes, but they give low scores of the other emotional dimension (disgust/fear) to each. In contrast, snake-fearful respondents not only give higher fear and disgust scores to the respective snake stimuli, but they also give high scores of fear to the disgust-eliciting snakes and high scores of disgust to the fear-eliciting snakes. Both Likert-scale scores and rank-ordering data show that the clear border dividing both snake stimuli categories dissolves when evaluated by the snake-fearful respondents.